Nickel hydroxide microsphere coated and injected with Ni-P alloy, preparation method and application thereof
By using the in-situ chemical reduction method of sodium phosphite reducing agent in alkaline zinc-nickel flow batteries, Ni-P alloy coating and injection of nickel hydroxide particles is solved, and the voltage efficiency and cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202111057000.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-09-09
AI Technical Summary
In existing alkaline zinc-nickel flow batteries, nickel hydroxide has poor conductivity, which makes it easy to generate γ-NiOOH with larger layer spacing during charging, resulting in nickel ball crushing and battery performance degradation.
In situ chemical reduction method using sodium hypophosphite as a reducing agent, the nickel hydroxide particles are coated and injected into Ni-P alloy, which improves the overall conductivity of nickel hydroxide microspheres and reduces the contact resistance between particles.
The voltage efficiency of alkaline zinc-nickel flow batteries is significantly improved, the integrity of nickel balls is maintained, the cycle stability is improved, and the preparation cost is reduced.
Smart Images

Figure CN115775891B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage batteries, and specifically relates to the field of alkaline zinc-nickel flow batteries, in particular to a highly conductive nickel hydroxide microsphere coated and injected with Ni-P alloy for alkaline zinc-nickel flow batteries, and a preparation method and application thereof. Background Art
[0002] Liquid flow battery energy storage technology is one of the efficient large-scale electrochemical energy storage technologies. It realizes the conversion between "electrical energy-chemical energy-electrical energy" and stores and releases electrical energy through the change of the valence state of the reactive substances dissolved in the electrolyte. Liquid flow battery energy storage technology can independently regulate the output power and energy storage capacity and has no special requirements for terrain. It has the advantages of long cycle life, short response time, high output power, safety and environmental protection. At present, all-vanadium liquid flow battery (VFB) is considered to have good application prospects due to its high safety, good stability, high efficiency and long life. However, the energy density of VFB is low and pentavalent vanadium is a highly toxic substance, which to a certain extent limits its large-scale application.
[0003] Alkaline zinc-nickel flow battery is a new type of large-scale energy storage battery. Both the positive and negative active materials are non-toxic and harmless. As a clean energy source, it has the advantages of high operating voltage, good safety and low cost. The positive active material is spherical nickel hydroxide, which is one of the key materials for alkaline zinc-nickel flow batteries and has the advantages of high tap density and high specific capacity. The α phase in spherical nickel hydroxide is unstable in alkaline solutions and easily ages to form a β phase. As a semiconductor material, nickel hydroxide itself has poor conductivity, so the stable β phase is easily overcharged to form γ-NiOOH with a larger interlayer spacing (such as Figure 1 ), resulting in nickel ball crushing and degradation of battery performance.
[0004] At present, the methods for improving the conductivity of nickel hydroxide mainly include surface chemical coating and chemical co-deposition. The surface chemical coating method mainly coats a layer of highly conductive CoOOH on the surface of nickel hydroxide particles, but it cannot cover the interior of nickel hydroxide microspheres, resulting in low conductivity inside the nickel hydroxide, and then overcharging on the surface and generating γ-NiOOH with a larger interlayer spacing, and causing the microspheres to pulverize and break, affecting battery stability. The chemical co-precipitation method of doping cobalt is beneficial to improving the conductivity inside the crystal, but the effect on improving the contact resistance between particles is still not obvious. Therefore, the research and development of new methods for preparing highly conductive nickel hydroxide microspheres has become an important topic that needs to be studied urgently. Summary of the invention
[0005] In view of the above technical problems, the purpose of the present invention is to provide a highly conductive nickel hydroxide microsphere coated and injected with Ni-P alloy, a preparation method thereof, and an application in an alkaline zinc-nickel liquid flow battery.
[0006] The present invention adopts an in-situ chemical reduction method using sodium hypophosphite as a reducing agent to coat and inject Ni-P alloy into nickel hydroxide particles. The coated and injected Ni-P alloy can not only improve the overall conductivity of the nickel hydroxide particles and ensure the integrity of the nickel balls during the charging process, but also reduce the contact resistance between the particles. The combined effect of the two can significantly improve the voltage efficiency of the alkaline zinc-nickel liquid flow battery. The preparation method of the nickel hydroxide microspheres coated and injected with Ni-P alloy provided by the present invention is low in cost, simple and convenient, easy to scale up, and has excellent battery performance and cycle stability, and is expected to achieve large-scale commercial production.
[0007] To achieve the above purpose, the specific technical solution adopted by the present invention is as follows:
[0008] A method for preparing nickel hydroxide microspheres coated and injected with Ni-P alloy mainly comprises the following steps:
[0009] (1) dissolving sodium hypophosphite in water to prepare a sodium hypophosphite solution with a concentration of 10 to 40 g / L, and storing the solution at 60 to 100° C.;
[0010] (2) adding nickel hydroxide powder to the sodium hypophosphite solution prepared in step (1), wherein the mass ratio of sodium hypophosphite to nickel hydroxide powder is (1:20) to (1:2), and stirring at 60 to 100° C. for 20 to 40 minutes;
[0011] (3) The solution obtained in step (2) is filtered to obtain a filter residue, which is then washed and dried to obtain nickel hydroxide microspheres coated and injected with Ni-P alloy.
[0012] Furthermore, in step (1), the concentration of the sodium hypophosphite solution is 20 to 30 g / L.
[0013] Furthermore, in step (2), the mass ratio of sodium hypophosphite to nickel hydroxide powder is (1:10) to (4:10).
[0014] Furthermore, the washing in step (2) is specifically rinsing with ultrapure water; and the drying temperature is 40 to 100°C.
[0015] Another aspect of the present invention provides nickel hydroxide microspheres coated and infused with Ni-P alloy prepared by the above preparation method.
[0016] The present invention also provides a method for preparing a nickel electrode, which mainly comprises the following steps:
[0017] (1) dissolving polyvinylidene fluoride (PVDF) in an organic solvent and stirring the mixture to obtain a binder having a polyvinylidene fluoride concentration of 40 to 100 g / L;
[0018] (2) The nickel hydroxide microspheres coated and injected with Ni-P alloy are dispersed in the binder prepared in step (1), wherein the mass ratio of the nickel hydroxide microspheres to polyvinylidene fluoride is (1:30) to (1:5), to obtain a dispersion containing the nickel hydroxide microspheres, and the porous electrode is completely immersed in the dispersion until the bubbles are completely discharged, and the electrode is taken out and dried to obtain a nickel electrode.
[0019] Furthermore, the organic solvent in step (1) includes dimethylacetamide and dimethylformamide.
[0020] Furthermore, the material of the electrode in step (2) is selected from graphite felt, carbon felt, carbon cloth and carbon paper.
[0021] Furthermore, the drying temperature in step (2) is 40-100°C.
[0022] The invention also provides a nickel electrode prepared by the preparation method.
[0023] The present invention also provides the use of the nickel hydroxide microspheres and / or nickel electrodes coated and injected with Ni-P alloy in alkaline zinc-nickel liquid flow batteries.
[0024] Furthermore, the positive and negative electrolytes of the alkaline zinc-nickel flow battery are completely the same, and are obtained by dissolving 0.4M ZnO in 3.8M NaOH and stirring thoroughly.
[0025] Furthermore, the negative electrode of the alkaline zinc-nickel flow battery is a porous carbon felt, and the positive electrode is a nickel electrode.
[0026] The beneficial effects of the present invention compared with the prior art are as follows:
[0027] (1) Currently, commercial nickel hydroxide mainly adopts the CoOOH coating strategy. On the one hand, this method can only coat the outer surface of nickel hydroxide and cannot penetrate into the interior. On the other hand, the price of Co element is high, which is not conducive to reducing costs. The present invention adopts an in-situ chemical reduction method using sodium hypophosphite as a reducing agent to coat and inject Ni-P alloy into nickel hydroxide particles. The preparation method of nickel hydroxide microspheres allows Ni-P alloy to not only coat the outer surface of nickel hydroxide secondary particles, but also inject into the interior of nickel hydroxide primary particles, thereby improving the overall conductivity of nickel hydroxide microspheres, facilitating the development of active substances inside nickel hydroxide particles, improving the uniformity of nickel hydroxide particle charging, preventing overcharging of particle surfaces, inhibiting the formation of γ-NiOOH phase during the cycle, preventing nickel ball fragmentation, maintaining the integrity of nickel balls, and improving cycle stability. The voltage efficiency of the alkaline zinc-nickel liquid flow battery assembled with the method is increased by 3%.
[0028] (2) The preparation method of the nickel hydroxide microspheres of the present invention is low-cost, simple and convenient, easy to scale up, and is expected to achieve large-scale commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.
[0030] Figure 1 Schematic diagram of the crystal form change of nickel hydroxide.
[0031] Figure 2 These are the EDC analysis diagrams and cross-sectional mapping diagrams of nickel hydroxide microspheres coated and injected with Ni-P alloy. a is the EDS analysis diagram of the untreated nickel hydroxide surface; b is the EDS analysis diagram of the nickel hydroxide surface coated and injected with Ni-P alloy; cf are the cross-sectional mapping diagrams of nickel hydroxide microspheres coated and injected with Ni-P alloy.
[0032] Figure 3 At 40mA / cm 2 Current density, 20mAh / cm 2 Performance comparison of alkaline zinc-nickel flow batteries assembled with nickel hydroxide coated and injected with Ni-P alloy prepared with different amounts of reducing agent added under the conditions of surface capacity.
[0033] Figure 4 At 40mA / cm 2 Current density, 20mAh / cm 2 SEM comparison of nickel electrodes prepared with untreated nickel hydroxide microspheres (a), commercial Co-coated nickel hydroxide microspheres (b), and nickel hydroxide microspheres coated and injected with Ni-P alloy (c) at the end of charging under the condition of surface capacity.
[0034] Figure 5 At 40mA / cm 2 Current density, 20mAh / cm 2 Comparison of the cycling performance of alkaline zinc-nickel flow batteries assembled with untreated nickel hydroxide electrode and nickel hydroxide electrode coated and infused with Ni-P alloy under the conditions of surface capacity.
[0035] Figure 6 A comparison chart of the rate performance of alkaline zinc-nickel flow batteries assembled with untreated nickel hydroxide electrodes and nickel hydroxide electrodes coated and infused with Ni-P alloy.
[0036] Figure 7 At 40mA cm -2 Under the conditions, XRD comparison diagram of untreated nickel hydroxide electrode and nickel hydroxide electrode coated and injected with Ni-P alloy after charging for 30 minutes. DETAILED DESCRIPTION
[0037] The present invention is described in detail below with reference to the embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.
[0038] The single cell in the embodiment is assembled in the following order: positive terminal plate, graphite current collector, positive electrode 3x3cm 2 Nickel felt, polybenzimidazole ion conductive membrane, negative electrode 3x3 cm 2 Carbon felt, graphite current collector, negative terminal plate.
[0039] Battery performance test: The flow rate of electrolyte in the battery is 60mL / min, constant capacity charging is adopted, and the current density is 40mA / cm 2 , the charging time is 30min, the charging protection voltage is 2.5V, and the discharge cut-off voltage is 0.8V.
[0040] Example 1
[0041] 1) Prepare sodium hypophosphite solution: dissolve 1g, 2g, and 3g of sodium hypophosphite in 80mL of water respectively, and keep the temperature at 80℃ in a water bath for 30min;
[0042] 2) adding 8 g of nickel hydroxide powder respectively, stirring in a water bath at 80° C. for 30 min, during which the highly conductive Ni-P alloy covers the surface of the spherical nickel hydroxide particles and is injected into the interior of the spherical nickel hydroxide particles to obtain a nickel hydroxide microsphere dispersion;
[0043] 3) The nickel hydroxide microsphere dispersion prepared in step 2) is filtered with filter paper, washed with 1 L of ultrapure water, and then dried in an oven at 80° C. to obtain nickel hydroxide microspheres coated and injected with Ni—P alloy.
[0044] from Figure 2 It can be seen that after chemical plating of Ni-P alloy, there is no obvious difference in the surface morphology of nickel hydroxide microspheres. The EDS analysis results show that there is P element on the surface of nickel hydroxide after chemical reduction, indicating that the Ni-P alloy is coated on the outer surface of the nickel hydroxide microspheres. From the cross-sectional Mapping diagram, it can be seen that the P element is evenly distributed inside the nickel hydroxide microspheres after chemical plating of Ni-P alloy, indicating that the Ni-P alloy is injected into the interior of the nickel hydroxide microspheres, indicating that the coating and injection strategy is successfully implemented.
[0045] Example 2
[0046] A nickel hydroxide electrode is prepared by using porous carbon felt as a substrate for a nickel electrode, which is prepared by the following steps:
[0047] First, 72 g of polyvinylidene fluoride (PVDF) was dissolved in 1 L of N, N-dimethylacetamide (DMAc) solvent and stirred thoroughly to obtain a binder; 6 g of nickel hydroxide microspheres coated and injected with Ni-P alloy synthesized at different sodium hypophosphite concentrations (12.5 g / L, 25 g / L, 37.5 g / L) prepared in Example 1 were dispersed in the above PVDF solution, and the porous carbon felt was completely immersed in the above dispersion until the bubbles were completely discharged, and placed in an oven at 80°C for complete drying to obtain a nickel electrode.
[0048] The positive and negative electrolytes are exactly the same and are prepared as follows:
[0049] Dissolve 0.4 M ZnO in 3.8 M NaOH and stir thoroughly to obtain a uniform electrolyte.
[0050] Alkaline zinc-nickel flow battery test conditions: the negative electrode is porous carbon felt, the positive electrode is a prepared nickel electrode, the positive and negative electrolytes are 50 mL, the separator is an ion exchange membrane made of a nitrogen-containing heterocyclic aromatic polymer, and the charge and discharge current density is 40 mA / cm 2 , surface capacity is 20mAh / cm 2 The test was carried out under the test conditions.
[0051] from Figure 3 It can be seen that when the concentration of sodium hypophosphite is low, the battery performance does not change significantly. When the concentration of sodium hypophosphite is high, too much nickel hydroxide is consumed. At the same time, the coating on the surface of nickel hydroxide is too thick, and the proton conduction path increases, resulting in a large decrease in battery performance. The optimal effect is achieved when the concentration of the reducing agent sodium hypophosphite is 25g / L. The coulomb efficiency of the alkaline zinc-nickel flow battery reaches 99%, the voltage efficiency reaches 86%, and the energy efficiency reaches 85%.
[0052] At the end of charging, the nickel felt was taken out, rinsed, freeze-dried, and the sample was subjected to SEM examination. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the nickel hydroxide microspheres prepared by the present application after coating and injection of Ni-P alloy all maintain a complete structure. In addition, the samples were subjected to XRD test. Figure 7 It can be seen that the nickel hydroxide microspheres coated and injected with Ni-P alloy did not show a diffraction peak of the γ phase at 12° at the end of charging, indicating that the strategy of coating and injecting Ni-P alloy can effectively improve the overall conductivity of the microspheres and the uniformity during charging, and inhibit the formation of the γ phase.
[0053] Example 3
[0054] The nickel-zinc flow battery assembled with nickel electrodes made of nickel hydroxide microspheres prepared at a sodium hypophosphite concentration of 25 g / L has a current density of 40 mA / cm 2 , surface capacity is 20mAh / cm 2 The battery cycle performance test was carried out under the conditions of Figure 5 As shown. Figure 5 It can be seen that the performance of the zinc-nickel flow battery has not significantly decayed after 100 cycles.
[0055] Example 4
[0056] The preparation method and process are the same as those in Example 3, except that the 2 , surface capacity is 20mAh / cm 2 The battery rate performance is as follows: Figure 6 shown.
[0057] from Figure 6 It can be seen that at 100mA / cm 2 At a current density of 2.5 MW, the voltage efficiency of the zinc-nickel flow battery still reaches 70%.
[0058] Comparative Example 1
[0059] A nickel hydroxide electrode was prepared by using porous carbon felt as a substrate for a nickel electrode, which was prepared by the following steps:
[0060] 6 g of commercial nickel hydroxide powder (Jilin Yarong Technology Co., Ltd.) was dispersed in 72 g / L PVDF DMAc solution, and the porous carbon felt was completely immersed in the above dispersion until the bubbles were completely discharged. The felt was placed in an oven at 80°C for complete drying.
[0061] The positive and negative electrolytes are exactly the same and are prepared as follows:
[0062] Dissolve 0.4 M ZnO in 3.8 M NaOH and stir thoroughly to obtain a uniform electrolyte.
[0063] At a current density of 40 mA / cm 2 , surface capacity is 20mAh / cm 2 The test was carried out under the test conditions. At the end of the charge, the nickel felt was taken out, rinsed, freeze-dried, and the SEM sample was obtained. The results are as follows Figure 4 As shown. Figure 4 It can be seen from the figure that some commercial nickel hydroxide particles have broken. In addition, XRD test of the sample shows that Figure 7It can be seen that the untreated nickel hydroxide microspheres have a γ-phase diffraction peak of 12° at the end of charging, indicating that they have poor conductivity and are prone to overcharging to generate γ-phase on the surface, resulting in the crushing of the nickel balls.
[0064] Comparative Example 2
[0065] The preparation method and process are the same as those of Comparative Example 1, except that pure nickel hydroxide (Shanghai Aladdin Biochemical Technology Co., Ltd.) is used. The SEM results of the nickel felt taken out at the end of charging are as follows: Figure 4 As shown, from Figure 4 It can be seen that the nickel balls of pure nickel hydroxide are completely broken.
[0066] from Figure 4 It can be seen that the coating and injection strategy significantly improves the electronic conductivity of nickel hydroxide particles, improves the distribution uniformity of β-NiOOH during charging, prevents overcharging to form γ-NiOOH phase, and maintains the integrity of nickel balls. Figure 5 It can be seen that the battery performance remains almost unchanged after 100 cycles. Figure 6 It can be seen that the battery has excellent rate performance, 100mA / cm 2 At a current density of 2.5 MW, the voltage efficiency of the zinc-nickel flow battery can still reach 70%.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing nickel hydroxide microspheres coated and injected with Ni-P alloy, characterized in that: The main steps include: (1) dissolving sodium hypophosphite in water to prepare a sodium hypophosphite solution with a concentration of 20 to 30 g / L, and storing the solution at 60 to 100° C.; (2) adding nickel hydroxide powder to the sodium hypophosphite solution prepared in step (1), wherein the mass ratio of sodium hypophosphite to nickel hydroxide powder is (1:20) to (1:2), and stirring at 60 to 100° C. for 20 to 90 minutes; (3) The solution obtained in step (2) is filtered to obtain a filter residue, which is then washed and dried to obtain nickel hydroxide microspheres coated and injected with Ni-P alloy.
2. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of sodium hypophosphite to nickel hydroxide powder is (1:10) to (4:10), and the stirring time is 20-40 minutes.
3. Nickel hydroxide microspheres coated and injected with Ni-P alloy obtained by the preparation method according to any one of claims 1 to 2.
4. A method for preparing a nickel electrode, characterized in that: The main steps include: (1) dissolving polyvinylidene fluoride in an organic solvent and stirring the mixture to obtain a binder having a polyvinylidene fluoride concentration of 40 to 100 g / L; (2) The nickel hydroxide microspheres coated and injected with Ni-P alloy as described in claim 3 are dispersed in the binder prepared in step (1), wherein the mass ratio of polyvinylidene fluoride to nickel hydroxide microspheres is (1:30) to (1:5), to obtain a dispersion containing nickel hydroxide microspheres, and the porous electrode is completely immersed in the dispersion until the bubbles are completely discharged, and the electrode is taken out and dried to obtain a nickel electrode.
5. The preparation method according to claim 4, characterized in that: The organic solvent in step (1) includes N,N-dimethylacetamide and N,N-dimethylformamide.
6. The preparation method according to claim 4, characterized in that: The material of the electrode in step (2) is selected from graphite felt, carbon felt, carbon cloth and carbon paper; the drying temperature is 40-100°C.
7. A nickel electrode prepared by the preparation method according to any one of claims 4 to 6.
8. Use of the nickel hydroxide microspheres coated and infused with Ni-P alloy as claimed in claim 3 and / or the nickel electrode as claimed in claim 7 in an alkaline zinc-nickel liquid flow battery.
9. The use according to claim 8, characterized in that: The negative electrode of the alkaline zinc-nickel liquid flow battery is a porous carbon felt, and the positive electrode is a nickel electrode.
Citation Information
Patent Citations
Nickel electrode and its manufacture
JP2000294236A